Public Service Quality and Building Coordinated Policy: An Analytical Study of Jamkesmas And Jamkesda Implementation - HARDINI, HEVI (Universitas Muhammadiyah Yogyakarta, 2013)
This study will examine the implementation of Jamkesmas (Jaminan Kesehatan Masyarakat-Health Insurance Schemefor People) and Jamkedsa (Jaminan Kesehatan Masyarakat Daerah-Health Insurance Scheme for Local People). Both areinno-vative policies in term of health financing, since they reflect more the spirit of insurance compared to the previouspolicies which were merely about financial aid. However, these policies do not reflect the ideals of policy coordination.Several theoretical reviews about social health insurance are applied to figure out the spirit of Indonesian health insurancesocio-logically and culturally. The Colebatch’s framework of vertical and horizontal dimensions of policy is used as themain tool of analysis for measuring whether both Jamkesmas and Jamkesda are categorized as coordinated policies or not.Qualitative research approach is used as the method in order to gain in-depth information about the current polemic ofJamkesmas and Jamkesda implementations. Qualitative analysis method is applied during the process of analysis. Thesecondary data will be collected, sorted, coded and analyzed. Those several steps aim to cross check the validity of each datafor answering the research questions. The result of this study shows that Jamkesmas and Jamkedsa lack of coordinationduring the process of policy making which has led to complicated problems at the implementation stage namely: thelawsuit/multiple interpretations of the law, unstructured policy stages at the vertical level, complicated problems athorizontal stages and conflict among institutional governments. Moreover, the nature of policy coordinationin Indonesia is still reactive. This fact causes policy inconsistency which has the effect of law uncertainty and poorquality of public services.